2019
DOI: 10.1108/medar-02-2019-0448
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the evaluation of the perceived value added by internal auditing

Abstract: Purpose The purpose of this study is to propose a framework for the evaluation of the perceived value internal audit functions add to their organisations. The framework is based on service quality measurement principles, specifically SERVPERF, which is applied to internal auditing. Design/methodology/approach Insights obtained from the literature on internal auditing and service quality disciplines were synthesised to identify and structure value-adding attributes of internal auditing. A thematic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…Previous studies that aimed to investigate service quality aspects in the accounting context used generic models (e.g., Parasuraman et al 1988 ). Because these models are not specifically related to accounting services, the studies obtained divergent findings (e.g., Botha and Wilkinson 2019 ; Fleischman et al 2017 ; Guthrie and Parker 2016 ). Our results show that the accounting service dimensions have specific attributes that need to be observed by professionals who want to identify the quality of the service provided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that aimed to investigate service quality aspects in the accounting context used generic models (e.g., Parasuraman et al 1988 ). Because these models are not specifically related to accounting services, the studies obtained divergent findings (e.g., Botha and Wilkinson 2019 ; Fleischman et al 2017 ; Guthrie and Parker 2016 ). Our results show that the accounting service dimensions have specific attributes that need to be observed by professionals who want to identify the quality of the service provided.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al ( 2016 ) also used this instrument and found that all the five dimensions were relevant. On the other hand, Botha and Wilkinson ( 2019 ) used the SERVPERF instrument to evaluate the perceived value added by internal audit functions. They used service quality as a proxy and argued that the SERVPERF dimensions appear to be relevant to audit services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, an effective internal audit function should contribute to the creation of the added value for the company by improving the effectiveness of risk management, control, and governance processes ( Botha and Wilkinson (2019) showed that internal auditing can add value by helping companies to achieve their economic objectives through their involvement in the risk management system and the implementation of their recommendations by the top management. Furthermore, Eden and Moriah (1996) found that the performance of bank branches in Israel significantly improved during the six months following the implementation of internal audit.…”
Section: Definition and Objectives Of Internal Auditmentioning
confidence: 99%
“…International Journal of Advanced Engineering, Management and Science, 7(11) -2021 This article can be downloaded from here: www.ijaems.com 14 ©2021 The Author(s). Published by Infogain Publication.…”
mentioning
confidence: 99%